3(2p-6)=6(4p+15)

Simple and best practice solution for 3(2p-6)=6(4p+15) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2p-6)=6(4p+15) equation:



3(2p-6)=6(4p+15)
We move all terms to the left:
3(2p-6)-(6(4p+15))=0
We multiply parentheses
6p-(6(4p+15))-18=0
We calculate terms in parentheses: -(6(4p+15)), so:
6(4p+15)
We multiply parentheses
24p+90
Back to the equation:
-(24p+90)
We get rid of parentheses
6p-24p-90-18=0
We add all the numbers together, and all the variables
-18p-108=0
We move all terms containing p to the left, all other terms to the right
-18p=108
p=108/-18
p=-6

See similar equations:

| 10-3x=4+2x | | 6(x-4)+3(x-7)=3 | | –(u−–4)=–10 | | 3(2n+4)=2(4n+3) | | 3(f-4)=0 | | 7=q2− –6 | | 8(a+6)=6(a+12) | | y=-2*10^-07*500^2+0.0006*500 | | 8x−2x+–11x+–9x=–14 | | 6(y+4)=5(y+6) | | y=-2^-07*500^2+0.0006*500 | | 12y-10=50 | | -9x=207 | | (3^3x-5)+21=0 | | y=-2E-07*500^2+0.0006*500 | | -4x²+4x+3=0 | | 3^3x-5+21=0 | | 5x-11=4(2x-2) | | 3^(3x-5)+21=0 | | 10x-15+9x+5=180 | | x=3+3/4 | | X^5-2x-3=0 | | 3^2x+5=9^x-2 | | 5x-3=1+8x+13 | | -(d-6)=0 | | 32=20-3h | | x^2(x-1)=4(2x-3) | | 6x-1+4x+11=90 | | b-10/2=-13 | | 3x=8+4x | | x^2(x-1)=4(x-3) | | 31-3b=4 |

Equations solver categories